Persuasive Techniques in Makeup and Skincare Video Advertisements - Windy Gusti Dwiyanti (UPT P2M Politeknik Negeri Malang, 2024)
Most video advertisements used certain linguistic styles and persuasive techniques in order to attract and persuade audiences. Unfortunately, not all makeup and skincare video advertisements use linguistic styles and persuasive techniques appropriately. Thus, the researcher decided to study the use of linguistic styles and persuasive techniques in successful makeup and skincare video advertisements. Therefore, the data sources used in this research were the advertisements of L’Oreal Paris and Rare Beauty (as the makeup video advertisements) and of Nivea, and Curology (as the skincare video advertisements). The research design used is case study which is a form of qualitative research. This study attempted to investigate what persuasive techniques are used in the makeup and skincare video advertisements. Based on the result analysis, the researcher found that familiar language, simple vocabulary, imperative, and present tense were the most frequently used in makeup and skincare video advertisement. Then, the persuasive techniques used in makeup and skincare video advertisements were pathos as the most frequently used, and ethos and logos as the least frequently used.